The separation of the church and state media an inquiry into the political economy of the Catholic church and government television - Manahan, Roll Jervis (2012)
"The Separation of Church and the State Media, as the title suggests, is a descriptive study of National Broadcasting Network's religious programming and how it relates to the Catholic Church, through the lens of political economy and public sphere. This thesis studies the political economic relationship between NBN and the Catholic Church. From that point, three major areas of study will be explored - programming, policies, and production process. Through this study, I aim to trace the power relationships and interdependence between the two institutions. These power relationships pave the way to a symbolic mutualism between the Catholic Church and National Broadcasting Network. The Catholic producer-block timers use NBN as a venue for airing their programs, and thus extend the reach of the physical Church's teachings. The government station benefits from it financially. This thesis will also look on ethical considerations in religious programming, and will examine NBN's programming as a whole. On the other hand, this thesis indirectly addresses the issues of the commodification of the sanctity of the Catholic Church and its teachings. Lastly, one significant point here is that this thesis tries to look on how the political economy between the Catholic Church and the State television affects the Philippine public sphere. Key informants interviews and document analysis were used as the main methods in research. Findings show that Church and NBN are, in many ways, politically and economically related and involved in each other's operations. This thesis shall explore, expose and provoke our Catholic sensibilities in the light of its relation to the television."